2016
DOI: 10.1177/0267659116669585
|View full text |Cite
|
Sign up to set email alerts
|

Whole body perfusion in patients undergoing frozen elephant trunk for type A acute aortic dissections

Abstract: The Frozen Elephant Trunk (FET) can be adopted in selected type A acute aortic dissections (TAAAD). During FET, a prolonged distal circulatory arrest exposes the spine and visceral organs to potential ischemic injuries. Antegrade distal aortic perfusion (ADAP) could minimize this risk: we describe the technical aspects of the simultaneous use of antegrade cerebral perfusion (ACP) and ADAP achieving a "Whole Body Perfusion" (WBP) during FET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…3 As previously reported, this procedure can be performed at 28°C: antegrade distal arterial perfusion, via a catheter placed within the FET stent, combined with antegrade cerebral perfusion via the brachiocephalic trunk and perfusion into the LSA results in WBP and a reduced total time for distal circulatory arrest. 1 We found that zone 1 debranching affords better technical feasibility than the traditional approach and it allows for a more proximal stent landing (online supplementary video 2) with less occlusion of intercostal vessels thereby mitigating the risk of spinal cord injury. A disadvantage with this method is that an additional anastomosis is required between the distal vascular graft and the distal aorta; however, WBP mitigates any potential-related hypoperfusion of the distal body.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…3 As previously reported, this procedure can be performed at 28°C: antegrade distal arterial perfusion, via a catheter placed within the FET stent, combined with antegrade cerebral perfusion via the brachiocephalic trunk and perfusion into the LSA results in WBP and a reduced total time for distal circulatory arrest. 1 We found that zone 1 debranching affords better technical feasibility than the traditional approach and it allows for a more proximal stent landing (online supplementary video 2) with less occlusion of intercostal vessels thereby mitigating the risk of spinal cord injury. A disadvantage with this method is that an additional anastomosis is required between the distal vascular graft and the distal aorta; however, WBP mitigates any potential-related hypoperfusion of the distal body.…”
Section: Discussionmentioning
confidence: 82%
“…The concept of whole-body perfusion (WBP) has been reported before. 1 Briefly, a pigtail catheter was placed through the left femoral artery into the true lumen up to the ascending aorta under transoesophageal echocardiography guidance. Following re-sternotomy, the ascending aorta and the neck vessels were carefully dissected.…”
Section: Case Reportmentioning
confidence: 99%
“…Graft infection is a disastrous complication after aortic repair with reported incidence of 0.2-5% and morbidity rates exceeding 35% [Cappabianca 2017;Heyes 2009;Kirkwood 2010;Smeds 2016;Touma 2014. ] The presence of tracheoesophageal fistula adds to this treatment challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The distal stent portion of the hybrid prosthesis was left intact, after securing a long safety margin away from the infected site. Once lower body perfusion [Cappabianca 2017] was established, the tracheoesophageal fistula was repaired with isolation and excision, and closure of the esophageal lesion was performed. A generous intercostal muscle flap was wrapped between the esophagus and the trachea to ensure durable closure.…”
Section: Case Reportmentioning
confidence: 99%
“…In Frankfurt, after completion of the arch repair and deairing, the graft was clamped, followed by reconstitution of full body perfusion [El-Sayed 2016]. In Bari, the lower body perfusion was established after deployment of the frozen elephant trunk prosthesis [Cappabianca 2017]. Proximal aortic repair followed during the rewarming period.…”
Section: Minimally Invasive Aortic Arch Repair: Technical Considerations and Mid-term Outcomesmentioning
confidence: 99%